Anesthesia Assistance in Colonoscopy: Impact on Quality Indicators - Liang, Min; Zhang, Xinyan; Xu, Chunhong; Cao, Junli; Zhang, Zongwang (Frontiers in Medicine, 2022)
Background: Adenoma detection rate (ADR) and polyp detection rate (PDR) are both indicators for colonoscopy quality. Improving ADR or PDR is critical for reducing the incidence and mortality of colorectal cancer (CRC). Although several studies have focused on identifying the factors that may influence ADR or PDR, the evidence remains limited and inconclusive. We conducted a retrospective study to evaluate the effect of anesthesia assistance (AA) on ADR or PDR in patients undergoing colonoscopy screening and identify risk factors affecting ADR or PDR. Methods: We reviewed electronic medical records of patients who underwent colonoscopy screening between May 2019 and August 2020. Patients were divided into two groups according to whether they received AA: patients in Group A underwent colonoscopy screening with AA, whereas patients in Group O underwent colonoscopy screening without AA. Propensity score matching (PSM) was utilized to account for differences in baseline characteristics. After, ADR and PDR were compared between the two groups. Binary logistic regression was employed to identify risk factors that affected ADR or PDR. Results: Of 9432 patients who underwent colonoscopy examination during the study period, 7170 were included in the final analyses (Group A = 5756 and Group O = 1414). After PSM, 736 patients remained in each group for analyses. There was no significant difference between groups A and O (P > 0.05) in ADR or PDR. Binary logistic regression indicated that the endoscopic device version (Olympus HQ290), equipment image-based technique and number of images were independent risk factors that affected ADR, and the age (50–59 years and 60–69 years), gender (male), high-risk status, endoscopist seniority (senior endoscopist), equipment image-based technique and number of images were all independent risk factors that affected PDR. Conclusions: We discovered that AA does not affect ADR or PDR. Despite improved patient satisfaction, using AA is unnecessary for improving colonoscopy quality. Endoscopists should consider all these factors as much as possible when performing colonoscopy screening.